the hardy boys mystery stories 36 the secret of pirates' hill - Dixon, Franklin W.; Franklin W. Dixon (New York Grosset & Dunlap, 1956)
The Secret of Pirates' Hill (Hardy Boys, Book 36) by Franklin W. Dixon is a mystery novel where brothers Frank and Joe Hardy investigate a dangerous, sunken treasure hunt. The story begins with the brothers skin diving near Pirates' Hill, where they are attacked by a mysterious diver who attempts to kill Frank by firing a spear through his air hose.
English